Trichostatin A, a Histone Deacetylase Inhibitor, Alleviates Eosinophilic Meningitis Induced by Angiostrongylus cantonensis Infection in Mice - Zhang, Yanhua; Xie, Hui; Tang, Wenyan; Zeng, Xingda; Lin, Yu; Xu, Lian; Xiao, Lihua; Xu, Jun; Wu, Zhongdao; Yuan, Dongjuan (Frontiers in Microbiology, 2019)
Histone deacetylase inhibitor (HDACi) has been used in the treatment of neurodegenerative or autoimmune diseases. Angiostrongyliasis cantonensis caused by Angiostrongylus cantonensis infection is an emerging zoonosis of human eosinophilic meningitis or meningoencephalitis. Progressive neuronal apoptosis is the pathological basis of behavioral dysfunctions in angiostrongyliasis cantonensis. Neurological defects after anthelmintic treatment for angiostrongyliasis cantonensis are still common. In this study, we examined the effects of trichostatin A (TSA), a HDACi, on eosinophilic meningitis induced by A. cantonensis in mice. Intragastric administration of TSA significantly ameliorated brain injury and decreased cognitive impairments in mice at 15 days post infection. TSA administration effectively reduced the inflammatory factor levels of iNOS, TNF-α, IL-5, IL-6, and IL-13 in infected mice. TSA treatment counteracted apoptosis with reduced expression levels of cleaved caspase-3, -4, -6, and RIP3 in A. cantonensis infected mice. In addition, TSA administration reduced total HDAC activity and increased the acetylation of histone H3 and H4 in the brain tissue of infected mice. The underlying mechanism of TSA on eosinophilic meningitis might be associated with decreased NF-κB p65 nuclear accumulation by inhibiting IκB phosphorylation. Furthermore, a co-expressive network of NF-κB p65 with 22 other genes was constructed according to our previous transcriptomic data in infected mice. We identified the correlations in the gene expression of NF-κB p65 with Lrp10, Il12rb1, Nfkbia, Ube2n, and Ube2d1 in infected mice after TSA administration. Thus, TSA has a protective effect on the progression of eosinophilic meningitis induced by A. cantonensis in mice.